2015
DOI: 10.1039/c5tc01735a
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature grown wurtzite InxGa1−xN thin films via hollow cathode plasma-assisted atomic layer deposition

Abstract: Hollow cathode plasma assisted atomic layer deposited InxGa1−xN alloys show successful tunability of the optical band gap by changing the In concentration in a wide range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 51 publications
0
20
0
1
Order By: Relevance
“…(023) reflections 16,17 of the hexagonal wurtzite phase of InN were observed. We note that changes in deposition temperature and plasma power do not alter the peak positions, while the intensity of the peaks increases with increasing deposition temperature.…”
Section: Resultsmentioning
confidence: 99%
“…(023) reflections 16,17 of the hexagonal wurtzite phase of InN were observed. We note that changes in deposition temperature and plasma power do not alter the peak positions, while the intensity of the peaks increases with increasing deposition temperature.…”
Section: Resultsmentioning
confidence: 99%
“…39,40 Recently, we have reported a and c axis lattice parameters of a ∼20 nm InN grown using HCPA-ALD as 3.50 and 5.61 Å, respectively. 23 For a thick InN film (∼48 nm) reported in the present case, shift of lattice parameters towards the ideal values of stain free InN indicates the relaxation of the film. Strain reduction with the increase in thickness of the polycrystalline InN thin films has been reported in the literature as well.…”
Section: Resultsmentioning
confidence: 99%
“…Towards this goal, we recently have demonstrated the low-temperature atomic layer deposition of ternary In x Ga 1−x N, B x Ga 1−x N, and B x In 1−x N alloys on Si substrates using a remotely integrated hollow-cathode plasma source. 23, 24 Nepal et al have reported atomic layer epitaxy (ALE) of InN thin films on sapphire, the conventional substrate material for III-nitride growth, utilizing quartz-based inductively coupled plasma source. 25 On the other hand, silicon, the material of choice for micro-electronics industry, offers cost-effective, large wafer-diameter, high-quality substrates with inherent CMOS manufacturing compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed self-limiting growth characteristics for PA-ALDgrown AlN, GaN, and InN can be found elsewhere. [28][29][30] Ultrasoniction for the lift-off process was carried out in a manual Bransonic MH 1.9 l ultrasonic cleaner (Branson-Emerson) at room temperature for 30-60 s. The final dry Aretch process was accomplished using a 4-in. wafer compatible ICP etch reactor (SPTS Technologies, ICP-F 615-LL) with an Ar flow of 20 sccm, while the coil and platen power were maintained as 450 and 100 W, respectively.…”
Section: A Materials Growth and Processingmentioning
confidence: 99%